Assessing parents' motives for talking about alcohol with their emerging adult children. (February 2022) - Napper, Lucy E.; Trager, Bradley M.; Turrisi, Rob; LaBrie, Joseph W.
Highlights: Parent motives for alcohol communication predicted communication frequency. The desire to prevent alcohol use and teach safe drinking were common motives. Results provide preliminary support for the construct validity of a motives measure. Abstract: Past research has explored the content and frequency of alcohol-specific communication between parents and their emerging adult children. The current study aimed to address a gap in the research by examining parents' motivation for discussing alcohol. To accomplish this, we developed a multidimensional Parent Motives for Alcohol Communication Scale (PMACS). A total of 633 parents completed the PMACS along with measures assessing communication frequency, communication content, attitudes toward drinking, relationship quality, and perceptions of child alcohol use. An Exploratory Factor Analysis yielded five core communication motives. Parents were commonly motivated by desires to prevent their child's alcohol use, to respond to their child's heavy drinking, to teach their child how to drink safely, to meet relationship needs or expectations, and by a family history of alcohol problems. After controlling for demographic factors, communication motives predicted frequency of alcohol-specific communication. The patterns of relationship among motives and conceptually related constructs provided preliminary support for the construct validity of the PMACS.